ANALYSIS OF METHODS AND DEVICES FOR INCREASING THE EFFICIENCY OF STORAGE OF OIL AND OIL PRODUCTS IN TANK TANKS - Chernova, O. T.; Martyniuk, R. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
During the storage of oil and petroleum products in tanks, significant bottom sediments of paraffin and various impurities accumulate over time. The sediment falls out within 1-2 months and compacts into a solid mass within about 6 months. When storing oil and petroleum products in tanks, there are two most popular methods of combating bottom sediments: periodic decommissioning of the tank (emptying), its preparation and removal of accumulated bottom sediments; the use of various additives and devices to prevent sedimentation.